1998
DOI: 10.1136/jcp.51.10.731
|View full text |Cite
|
Sign up to set email alerts
|

Persistent damage to Enterocytozoon bieneusi, with persistent symptomatic relief, after combined furazolidone and albendazole in AIDS patients.

Abstract: Aim-Toinvestigate morphological changes in Enterocytozoon bieneusi and the duration of symptomatic relief after combination treatment with furazolidone and albendazole in AIDS patients. Methods-Four severely immunocompromised AIDS patients with symptomatic E bieneusi infection of the gut received an 18 day course of combined furazolidone and albendazole (500 + 800 mg daily). All patients were monitored for parasite shedding in stool by light microscopy at the end of treatment and monthly during follow up. At t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Furazolidone, on the other hand, was found to provide symptomatic relief and decreased parasite shedding but not eradication in the stools of six patients with AIDS and E. bieneusi [129]. A further study by the same group using the combination of this drug with albendazole again failed to demonstrate eradication of the parasite [130]. Finally, a single case report has suggested that nitazoxanide may be effective in the treatment of E. bieneusi [131].…”
Section: Microsporidiosismentioning
confidence: 91%
“…Furazolidone, on the other hand, was found to provide symptomatic relief and decreased parasite shedding but not eradication in the stools of six patients with AIDS and E. bieneusi [129]. A further study by the same group using the combination of this drug with albendazole again failed to demonstrate eradication of the parasite [130]. Finally, a single case report has suggested that nitazoxanide may be effective in the treatment of E. bieneusi [131].…”
Section: Microsporidiosismentioning
confidence: 91%
“…Albendazole is effective in treating E intestinalis but not very effective in treating E bieneusi. 73 74 Uncontrolled studies have shown the following agents to have some benefit in treating microsporidia: atovaquone, 75 furazolidone, 76 furazolidone-albendazole, 77 and thalidomide. 78 C cayetanensis infection can be treated effectively with TMP-SMX.…”
Section: Persistent Diarrhoeamentioning
confidence: 99%
“…Multiorgan E. bieneusi microsporidiosis involving the respiratory or the biliary tract has been reported [304,305]. Microsporidiosis in AIDS patients can be quantified by counting spores in stool and in smallbowel biopsy, because a strict correlation, varying greatly from patient to patient, exists between fecal (From [310] with permission) spore contents and duodenal biopsy spore counts [306]. Therapeutic options are still limited.…”
Section: Microsporidiosismentioning
confidence: 99%
“…bieneusi is currently available [254]. Recently, however, limited experience has suggested that combined treatment with furazolidone and albendazole may be effective against E. bieneusi, as correlations between persistent clinical remission and persistent decrease in parasite load both in tissue and in stool, along with morphological changes in the protozoan, have been documented [309,310] (Figs. [121][122][123][124][125].…”
Section: Microsporidiosismentioning
confidence: 99%